Misaligned needs: A study of CSR from an NGO and corporate perspective - Hidden, Karen (Research of GSB, 2017)
From a global perspective Corporate Social Responsibility (CSR) has been highlighted by business and society alike as essential. However, there is a growing concern surrounding the misalignment of funded and failed projects between business and Non-Governmental Organisations (NGOs). Literature indicates that often projects are initiated by the corporate donor without taking into consideration the need and long-term impact their investment might have on the selected NGO and the community that NGO supports (Blowfield & Frynas, 2005; Blundin, 2012; Kanter, 1999; Salang & Molebatsi, 2012). Furthermore, there is little emphasis on the role the NGO could play in the CSR granting process. The current research explores the role of CSR in business, the role of NGOs and the problems arising from the misalignment between the two. This paper questions the strategic alignment of CSR between business and NGOs and argues that something needs to change to form a cohesive and mutually sustainable model of engagement. A combination of phenomenology and Grounded Theory were used as the methodological frameworks for this research in order to understand how strategic alignment might result in a cohesive and sustainable match for the business and the NGO in the grant making and grant requesting phase. Justification for the use of blended methodologies is discussed in the study. The research examined the role of Dell South Africa's CSR processes and two of their NGO beneficiaries namely Christel House South Africa (CHSA) and Students Health and Welfare Centre Organization (SHAWCO). Staff from various levels within each of the above mentioned organizations formed part of the sample group. Semi-structured face-to-face and telephonic interviews were used to gather the research data, which was then analyzed and developed into codes using NVivo. The validity, reliability and justification surrounding the research have also been addressed. Eight key categories namely goal and vision alignment, strategic intent, communication, value creation, relevance and ROI, harsh realities, sustainability and impact and monitoring and evaluation, emerged from the data analysis and a model, based on the traditional Business Model Canvas, was developed. This model acts as a visual tool for corporates and NGOs when going through the CSR granting process and suggests that it should form the basis for a strategically aligned and cohesive fit between the two entities. Implications for corporates, NGOs and academics as well as areas for future research have also been outlined.